Concretos refratários nanoligados para aplicação em unidades de craqueamento catalítico - Prestes, Eduardo (Universidade Federal de São Carlos, 2013)
In the petrochemical industry gasoline and LPG are produced in the fluid catalytic cracking unit (FCCU). The cracking occurs by the contact of crude oil with fluidized fine particles of a ceramic catalyst. The process profitability is strongly related to a reduced number of the FCCU maintenance halts. In this sense, the refractory material performance is a key factor to increase the equipment working life. Nowadays, in the refractory market, castables specially designed for FCCU are not common. One aspect that induces this scenario is the difficulty to attain optimized properties in the temperature range compatible with the process conditions, not above 900ºC. One alternative to solve this problem is the addition of nanometric size particles in the castables composition. This can be carried out by replacing calcium aluminate cement (CAC) by colloidal silica. The high specific surface area provides an increase in the system reactivity, resulting in high mechanical resistance during the refractory firing step. Another possibility is the use of sintering additives which can help the densification at low temperatures. The synergism between nanoparticles reactivity and sintering effectiveness allows the development of high-performance nanobonded antierosive castables. In this context, colloidal silica bonded castables containing tabular alumina, fused silica or mullite grog and specific sintering additives were designed for FCCU riser application. Compared with the commercial reference products currently used by Brazilian petrochemical industry, the nanobonded materials presented superior performance for the main usual properties. Based on this novel technology an innovative mullite grog self-flow castable was developed. This material associates an intermediate apparent density value, between the tabular alumina and fused silica ones, with a low thermal conductivity and high thermal shock resistance.
Nano-bonded castables for fluid catalytic cracking units
Keywords: Concreto; Concretos refratários; Sílica coloidal; Indústria petroquímica; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA